A prospective cohort study comparing household contact and water Vibrio cholerae isolates in households of cholera patients in rural Bangladesh. - Christine Marie George; Khaled Hasan; Shirajum Monira; Zillur Rahman; K M Saif-; Mahamud-Ur Rashid; Fatema Zohura; Tahmina Parvin; Md Sazzadul Islam Bhuyian; Md Toslim Mahmud; Shan Li; Jamie Perin; et al. (Public Library of Science (PLoS), 2018)
BACKGROUND:Household contacts of cholera patients are at a 100 times higher risk of developing cholera than the general population. The objective of this study was to examine the incidence of V. cholerae infections among household contacts of cholera patients in a rural setting in Bangladesh, to identify risk factors for V. cholerae infections among this population, and to investigate transmission pathways of V. cholerae using multilocus variable-number tandem-repeat analysis (MLVA). METHODOLOGY/PRINCIPAL FINDINGS:Stool from household contacts, source water and stored water samples were collected from cholera patient households on Day 1, 3, 5, and 7 after the presentation of the index patient at a health facility. Two hundred thirty clinical and water V. cholerae isolates were analyzed by MLVA. Thirty seven percent of households had at least one household contact with a V. cholerae infection. Thirteen percent of households had V. cholerae in their water source, and 27% had V. cholerae in stored household drinking water. Household contacts with V. cholerae in their water source had a significantly higher odds of symptomatic cholera (Odds Ratio (OR): 5.49, 95% Confidence Interval (CI): 1.07, 28.08). Contacts consuming street vended food had a significantly higher odds of a V. cholerae infection (OR: 9.45, 95% CI: 2.14, 41.72). Older age was significantly associated with a lower odds of a V. cholerae infection (OR: 0.96, 95% CI: 0.93, 0.99). Households with both water and clinical V. cholerae-positive samples all had isolates that were closely related by MLVA. CONCLUSIONS/SIGNIFICANCE:These findings emphasize the need for interventions targeting water treatment and food hygiene to reduce V. cholerae infections.